Cetacean Habitat Selection in the Alaskan Arctic during Summer and Autumn - Moore, Sue E.; DeMaster, Douglas P.; Dayton, Paul K. (ARCTIC, 2000)
Ten years (1982-91) of sighting data from aerial surveys offshore of northern Alaska were analyzed to investigate seasonal variability in cetacean habitat selection. Distinct habitats were described for bowhead whales (Balaena mysticetus), white whales (Delphinapterus leucas), and gray whales (Eschrichtius robustus) on the basis of habitat selection ratios calculated for bathymetric and ice cover regimes. In summer, bowheads selected continental slope waters and moderate ice conditions; white whales selected slope and basin waters and moderate to heavy ice conditions; and gray whales selected coastal/shoal waters and open water. In autumn, bowheads selected inner shelf waters and light ice conditions; white whales selected outer shelf and slope waters and moderate to heavy ice; and gray whales selected coastal and shoal/trough habitats in light ice and open water. Habitat differences among species were significant in both seasons (ANOVA F > 28, p < 0.00001). Interseasonal depth and ice cover habitats were significantly different for bowhead whales (p < 0.00002), but not for gray whales (p > 0.35). White whale depth habitat was significantly different between seasons (p < 0.00002), but ice cover habitat was not (p < 0.08). Des données d'observation réalisées sur dix années (1982-1991) grâce à des relevés aériens au large de l'Alaska septentrional ont été analysées dans le cadre de recherches sur la variabilité saisonnière dans la sélection de l'habitat des cétacés. On a décrit des habitats distincts pour la baleine boréale (Balaena mysticetus), la baleine blanche (Delphinapterus leucas) et la baleine grise de Californie (Eschrichtius robustus) en se fondant sur les taux de sélection de l'habitat calculés pour le régime bathymétrique et celui de la couverture de glace. En été, la baleine boréale choisissait les eaux de la pente continentale et des conditions de glace modérée; la baleine blanche choisissait les eaux de la pente continentale et du bassin océanique, et des conditions de glace ...